Social Capital in Utilizing Clean Water (Case Study: Pagak District, Malang Regency) - Dzvimbo, Munyaradzi A; Rahmawati; Auliah, Aidha; Chanda, Moses; Ari, Ismu Rini Dwi; Ken Sugou; Sari, Indah Cahayaning (Perencanaan Wilayah dan Kota FT UB, 2023)
Social capital is a key element in sustainable development and natural resource management. In the context of clean water management, an in-depth understanding of social capital can reveal the dynamics of social interactions between individuals and groups in the community. Social capital includes aspects of trust, social networks, and social norms that shape the way people interact and cooperate. This research aims to evaluate the condition of community social capital in utilizing clean water in Pagak District through SEM-PLS analysis. A questionnaire survey was conducted on 267 households, distributed proportionately in each village in Pagak District. The research results show that most of the factors studied reflect the condition of social capital. However, there are several factors that were considered immaterial and were removed from the analysis model. These factors include trust in individuals with different ethnic or cultural backgrounds, cultural activities in the village, and payment of water source maintenance fees. This research emphasizes the need for a holistic and collaborative research approach to understand the social capital of village communities in the context of clean water management, involving various scientific disciplines and stakeholders.